THE COMPATIBILITY OF READING EXERCISES WITH BLOOMâS REVISED TAXONOMY AND 2013 CURRICULUM (A Case of English Textbook Entitled BahasaInggrisfor Grade XI Published by Department of National Education 2014) - Arvianto, Zuhrian Ivan; Faridi, Abdurrahman (English Education Journal, 2016)
This study is aimed at identifying the cognitive processes and knowledge dimension of the Revised Bloom Taxonomy involved in the reading exercises; determining how the Lower Order Thinking Skills and Higher Order Thinking Skills are realized through the reading exercises; and determining how the reading exercisesin the textbook are compatible with 2013 curriculum. The English  textbook being analysed is âBAHASA INGGRISâ for grade XI published by the Department of National Education 2014. The results concluded that (1) there are only three cognitive processes found: Remember, Understand and Evaluate, indicate that the reading exercises are not in hierarchical order. (2) There are two knowledge dimensions found: factual knowledge and metacognitive knowledgeimplythat the knowledge dimension offered is not varied. (3) The reading materials promote more Lower Order Thinking Skills than Higher Order Thinking Skills. (4) The reading exercises in the textbook is less compatible with 2013 curriculum. Each chapter presents only one reading text and it lacks of information on the generic structure and the linguistics features of the related text. A textbook should not only be compatible with the current curriculum, but also have a characteristic of cognitive development and critical thinking.